Peluang Lembaga Dakwah dalam Kewirausahaan dan Inovasi di Era Disruptif - M. Miftahur Rahmat Isnaini; Cecep Castrawijaya (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This disruptive era marked by technological advances and social change provides both challenges and opportunities for da'wah institutions. This research aims to explore the role of da'wah institutions in entrepreneurship and innovation as a strategy to increase relevance and social impact. The method used is qualitative with a library research approach, analyzing relevant literature about social entrepreneurship and innovation in the context of da'wah. The research results show that da'wah institutions can utilize social entrepreneurship to empower communities, create independent resources, and reduce dependence on external donations. In addition, the integration of information and communication technology in da'wah allows the communication of messages that are more interesting and effective, especially to the younger generation. However, da'wah institutions must also be ready to face challenges such as changes in people's mindsets and high competition. This research recommendation includes innovative development strategies and collaboration with the private sector to strengthen entrepreneurship programs. With the right approach, it is hoped that da'wah institutions can make a significant contribution to society in this ever-changing era.